Does Alt-RAMEC protocol and facemask treatment affect dentoalveolar structures? A 3-dimensional study - ÖNEM ÖZBİLEN, ELVAN; YILMAZ, HANİFE NURAY (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2021)
Objectives: To evaluate dentoalveolar changes immediately after the alternate rapid maxillary expansion and constriction (Alt-RAMEC) protocol and facemask (FM) treatment using cone-beam computed tomography images. Materials and Methods: Cone-beam computed tomography images of 20 patients (mean age = 9.64 +/- 1.3 years) who received the Alt-RAMEC protocol before FM treatment were retrieved in this retrospective study. Dental and alveolar inclinations, buccal and palatal alveolar bone thickness, and buccal and palatal alveolar bone height changes were measured before treatment (T0), after the Alt-RAMEC protocol (T1), and after FM treatment (T2). Measurements for right and left molars were performed separately. The Shapiro-Wilks test was used to assess the conformity of the parameters to the normal distribution. The paired t-test and repeated measures analysis of variance were used for normally distributed data. The Wilcoxon signed-rank test and Friedman test were used for non-normally distributed data. The Bonferroni correction was used to reduce the chances of obtaining false-positive results. Statistical significance was set at P < .05. Results: Buccal alveolar bone thickness and alveolar bone inclinations decreased significantly from T1 to T0 and showed no significant change from T2 to T1. The total reduction T2-T0 was statistically significant. The change in palatal alveolar bone thickness was not significant T1-T0 but increased significantly for T2-T1 and T2-T0. Buccal alveolar bone height, palatal alveolar bone height, and molar inclinations increased significantly T1-T0, but there was no significant change T2-T1. The total reduction at T2-T0 was statistically significant. Conclusions: The results of this study revealed that the effects of the Alt-RAMEC protocol on dentoalveolar tissues were similar to the changes reported in the literature after rapid palatal expansion.
Keywords: Alt-Ramec; Cone-beam CT; Dentoalveolar; Maxillary expansion; Maxillary hypoplasia; Angle Class III; RAPID MAXILLARY EXPANSION; BEAM COMPUTED-TOMOGRAPHY; TOOTH-BORNE EXPANDERS; ALVEOLAR BONE HEIGHT; TISSUE-BORNE; ACCURACY